Assessment of drought hazard change in China under 2°C, 3°C and 4°C temperature rise scenarios based on CMIP6 models - Xiufang Zhu; Dongyan Lu; Tingting Liu; Shizhe Zhang (Geomatics, Natural Hazards & Risk)
Understanding drought responses to global warming can enhance our ability to manage drought risks. In this study, the standardized precipitation evapotranspiration index was computed using 18 climate models from the Coupled Model Intercomparison Project Phase 6 (CMIP6). Three drought characteristics (drought frequency, duration, and intensity) were extracted, and the drought hazard index (DHI) was constructed to assess drought hazards in China for the 1995–2014 reference period and future 2 °C, 3 °C and 4 °C temperature rise scenarios. Results revealed that drought frequency in the eastern monsoon region of China was higher in the south, lower in the north, and generally increased with warming. Drought duration and intensity were higher in northwest China and lower in southeast China, markedly increasing with warming. The DHI was relatively high in northwest inland and southeast coastal China. National average DHI values for the reference period and the three temperature rise scenarios were 0.26, 0.31, 0.33, and 0.36, respectively. Under future temperature rise scenarios, the DHI in all regions of China, excluding the southeastern Qinghai-Tibet Plateau, would generally increase compared to the reference period. National average increase values of DHI under the 3 °C and 4 °C scenarios reach 1.5 and 2 times that under the 2 °C scenario.